Heart rate variability for early detection of iron overload cardiomyopathy in β-thalassemia patients - Nut Koonrungsesomboon (2018)
© 2015 Informa Healthcare USA, Inc. Iron overload cardiomyopathy remains the major cause of death in β-thalassemia (β-thal). Conventional routine screening parameters such as serum ferritin and echocardiogram (ECG) do not permit early detection of this condition. Although non-transferrin-bound iron (NTBI) is a reliable indicator for iron overload, it is still not universally available. Recently, heart rate variability (HRV), representing cardiac autonomic function, was found to be depressed in thalassemia patients. We hypothesized that HRV can be used for early detection of iron overload cardiomyopathy. Fifty patients (aged 29 ± 11 years; 31 females and 19 males) with β-thal were enrolled. The 24-hour Holter monitoring for HRV, serum ferritin, NTBI, hematological values and ECG were performed for each patient. Of the 50 patients, 29 carried β-thal major (β-TM). Non-transferrin-bound iron was weakly correlated to all time-domain HRV parameters. Low- and high-frequency domain HRV parameters were also inversely weakly correlated with NTBI. Neither HRV nor NTBI was correlated with serum ferritin. With its weak but significant correlation with NTBI, HRV may be considered to be used as a potential indicator of an iron overload condition and an early marker of cardiac involvement in patients with β-thal.